Sweltsa naica - Stark, Bill P.; Kondratieff, Boris C.; Kirchner, Ralph F.; Stewart, Kenneth W. (Zenodo, 2011)
Sweltsa naica (Provancher) (Figs. 16-20) Perla naica Provancher, 1876:214. Holotype ♂ (Quebec Provincial Museum), vicinity of Quebec City Alloperla novascotiana Needham & Claassen, 1925:113. Holotype ♂ (Cornell University), Nova Scotia, Truro, synonymy by Ricker, 1952 Material examined. NEWFOUNDLAND: Bowed Brook, Hwy 430, Bellburns, 5 June 1998, B.C. Kondratieff, R. W. Baumann, 13♂, 1 pharate larva (CSU). PENNSYLVANIA: Westmoreland Co., Powdermill Run, Powdermill Nature Reserve, 15 May 1993, S.A. Grubbs, 6♂, 2♀, 7 larval skins (WKU). Same site, 16 May 1993, S.A. Grubbs, 21♂, 13♀, 5 larval skins (WKU). Mature larva. Body length 10 mm. General color brown, head darker over frons (Fig. 16). Pronotum bearing ca. 14 anterolateral setae and ca. 19 posterolateral setae near margin; posterolateral row extends to median suture. Mesonotum bearing ca. 13 prominent outer marginal setae and metanotum bearing ca. 17 prominent outer marginal setae (Fig. 17); intercalary surface of metanotal wingpad with numerous setae. Fore femora with numerous thick setae in basal half and along dorsal margin (Fig. 18); dorsal margin with a few fringe setae. Tibiae with outer fringe setae and inner row of thick setae. Posterior abdominal fringe on tergum 8 with median field occupied by a small group of thin setae, tergum 9 fringe with thick setae in median field (Fig. 19). Cerci with ca. 15 segments; long dorsal setae in segmental whorls about as long as 2 segments (Fig. 20); most apical segments with several long setae visible in profile. Comments. The distinctive shoehorn shaped male epiproct for S. naica suggests it is not closely related to other eastern Nearctic members of the genus, however Surdick (2004) presents evidence which support the species being more closely related to members of the S. onkos complex than to S. oregonensis (Frison) or other western species with similar epiproct structure. Geographically, S. naica is known from West Virginia and Virginia, north through Atlantic Canada (Surdick 2004), where it is often sympatric with S. onkos and sometimes with S. lateralis . Larvae of S. naica are generally similar to those of S. onkos , particularly in sharing long dorsal cercal setae (Fig. 20) and long tibial fringe (Fig. 19), but pre-emergent larvae of the two are distinguished on the basis of abdominal and occipital pigment patterns. Sweltsa naica larvae are the only eastern Nearctic Sweltsa species known to have a dark frons and a relatively pale occipital area. : Published as part of Stark, Bill P., Kondratieff, Boris C., Kirchner, Ralph F. & Stewart, Kenneth W., 2011, Larvae Of Eight Eastern North American Sweltsa (Plecoptera: Chloroperlidae), pp. 51-64 in Illiesia 7 (4) on page 56, DOI: 10.5281/zenodo.4760403 : {"references": ["Provancher, L. 1876. Petite faune entomologique du Canada. Nevropteres. Naturaliste Canadien, 8: 177 - 191, 209 - 218.", "Ricker, W. E. 1952. Systematic studies in Plecoptera. Indiana University Publications, Science Series No. 18. Indiana University Press, Bloomington, Indiana. 200 pp.", "Surdick, R. F. 2004. Chloroperlidae (The Sallflies). Pp. 1 - 60 in Stark, B. P. & B. J. Armitage [editors]. Stoneflies (Plecoptera) of eastern North America. Volume II. Chloroperlidae, Perlidae, and Perlodidae (Perlodinae). Bulletin of the Ohio Biological Survey, New Series, Volume 14. Ohio Biological Survey, Columbus, Ohio. 192 pp."]}